Pola Makan dan Stres dengan Kejadian Gastritis Mahasiswa Program Studi Ilmu Keperawatan Stik Siti Khadijah - Septi Viantri Kurdaningsih; M Ramadhani Firmansyah (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2021)
Gastritis is a digestive tract disorder caused by damage or erosion, inflammation of the gastric mucosa which can be caused by the consumption of drugs such as acetaminophen, aspirin, and corticosteroid steroids, physical activity, stress and diet. Gastritis can cause stomach bleeding and even become cancer. This study aims to determine the relationship between eating pattern and stress with the incidence of gastritis in students of the Nursing Science Study Program at STIK Siti Khadijah Palembang. The research design used a descriptive analysis study with a cross sectional research approach. The sampling technique in this study used Simple Random Sampling with a sample of 51 respondents. The statistical test used the chi square test. The results showed that there were 28 adult respondents (54.9%) more than 23 adolescent respondents (45.1%), 45 female respondents (88.2%) more than 6 male respondents (11.8%), 29 poor eating patterns respondents (56.9%) more than 13 good eating patterns respondents (25.5%) and bad eating patterns as many as 9 respondents (17.6%), respondents with mild stress were 39 respondents (76.5%) more than respondents with moderate stress were 12 respondents (23.5%), respondents who experienced gastritis were 29 respondents (56, 9%) more than respondents who did not experience gastritis as many as 22 respondents (43.1%). There is a relationship between eating pattern and the incidence of gastritis, p-value 0.014, there is a relationship between stress and the incidence of gastritis, p-value 0.026. It is expected for students to be able to maintain their diet and avoid stress that can cause gastritis